2015
DOI: 10.1089/dna.2014.2712
|View full text |Cite
|
Sign up to set email alerts
|

Expression of POSTN, IL-4, and IL-13 in Chronic Rhinosinusitis with Nasal Polyps

Abstract: Chronic rhinosinusitis with nasal polyps (CRSwNP) is one of the most frequently encountered chronic nasal diseases with a significant impact on patient quality of life. The aim of our study was therefore to investigate the association between the POSTN, IL-4, and IL-13 gene expression and the nasal polyp development. The objective of this study was to determine differential expression of POSTN, IL-4, and IL-13 genes in the mucosa and polyps of 63 patients with CRSwNP and 23 chronic rhinosinusitis (CRS) without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 40 publications
(41 reference statements)
1
19
0
2
Order By: Relevance
“…Pendrin knockout is also associated with reduced lung inflammation in a murine model of Bordetella pertussis lung infection (26). IL-13, the cytokine used commonly in in vitro and animal models of airway inflammation, is elevated in CF, asthma, chronic rhinosinusitis, viral and certain bacterial infections, and chronic obstructive pulmonary disease, and in response to cigarette smoke (27)(28)(29)(30)(31)(32)(33)(34). In murine models of asthma, pendrin knockout reduces pulmonary pathology, airway hyperreactivity, and immune cell infiltration, while pendrin overexpression increases airway hyperreactivity (10,11).…”
mentioning
confidence: 99%
“…Pendrin knockout is also associated with reduced lung inflammation in a murine model of Bordetella pertussis lung infection (26). IL-13, the cytokine used commonly in in vitro and animal models of airway inflammation, is elevated in CF, asthma, chronic rhinosinusitis, viral and certain bacterial infections, and chronic obstructive pulmonary disease, and in response to cigarette smoke (27)(28)(29)(30)(31)(32)(33)(34). In murine models of asthma, pendrin knockout reduces pulmonary pathology, airway hyperreactivity, and immune cell infiltration, while pendrin overexpression increases airway hyperreactivity (10,11).…”
mentioning
confidence: 99%
“…IL-4, a Th2 cytokine with an antiinflammatory effect, is one of the most studied cytokines of CRSwNP. The increased IL-4 level in nasal polyposis has been reported in several studies [37]. Milonski et al demonstrated increased IL-4 gene expression in atopic patients with CRSwNP [38].…”
Section: Discussionmentioning
confidence: 75%
“…IL-4 ist in der Lage, die Differenzierung von CD4 +-T-Zellen in T H 2-Zellen zu fördern und gleichzeitig die IFN-γ-Produktion und T H 1-Antwort zu inhibieren [6]. Darüber hinaus kann die erhöhte Anwesenheit von IL-4 und IL-13 eine Rolle bei der Hochregulierung des vaskulären Zelladhäsionsmoleküls 1 (VCAM-1) spielen, was die weitere Infiltration von Eosinophilen in das Gewebe erleichtert [14][15][16]. Im Vergleich zur Rolle von IL-5 bei der CRSwNP ist die Datenlage bei IL-4 und IL-13 eher spärlich.…”
Section: Il-4/il-13 Und Deren Rezeptorenunclassified
“…Die Ergebnisse mehrerer Untersuchungen weisen darauf hin, dass die Beziehung zwischen den beiden Zytokinen IL-4 und IL-13 und der Bildung von nasalen Polypen nicht notwendigerweise mit der Induktion einer eosinophilen Entzündung verbunden ist [14]. Des Weiteren scheint IL-4 nur in Untergruppen von CRSwNP mit dem Samter-Trias-Phänotyp oder bei Komplikationen durch Allergien wie dem anaphylaktischen Schock eine wichtige pathogene Rolle zu spielen [14,19]. Therapeutische Antikörper sind für gewöhnlich Gamma-Immunglobuline (IgG).…”
Section: Il-4/il-13 Und Deren Rezeptorenunclassified